Molecular classification of autofluorescence excision margins in oral potentially malignant disorders. (13th March 2018) - Farah, C S; Kordbacheh, F; John, K; Bennett, N; Fox, S A
Abstract : Objective: To define molecular differences between autofluorescence and white light defined excision margins in oral potentially malignant disorders (OPMD) using transcriptome expression profiles. Materials and methods: Excisional biopsy specimens were taken from 11 patients at three different sites for each lesion: centre, white light margin and autofluorescence margin. The lesions were diagnosed histopathologically as oral epithelial dysplasia, oral lichenoid dysplasia, oral lichen planus or other. Transcriptome analysis was performed by RNA sequencing, hierarchical clustering, differential expression and biological pathway analysis. Results: For hierarchical clustering, the samples broadly clustered according to histology rather than the margins with lichenoid samples clustering together. Differential expression analysis showed that independent of histology, there was greater molecular dysregulation between the lesion centre and autofluorescence margin compared to the lesion centre and white light margin. Furthermore, the autofluorescence and white light margins were molecularly distinct, indicating the white light margins harboured abnormality. Conclusion: Our results indicate that the molecular profile of OPMD changes with divergence away from the centre of the lesion, and that autofluorescence determined margins are superior to the white light margin in achieving a clear molecular margin when excising an OPMD.